(3JGQjN eOjfI OeTbs - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3jHOC HJQLeI dGMb Hf GdMSjf Hf YeQGf s
(3BNQgG (B:s
(3hjfJgi HJQLeI jRjO Hf eYGhjI s
(3Ydbg CMeO fYeI Gddg GdCTehfis
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B331 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B29 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs